Impact of HCV antiviral therapy on the Liver Transplantation Waiting-List assessed by mathematical models - Eleazar Chaib; Joao Luis Erbs Pessoa; Marizete Medeiros; Eduardo Massad (Journal of Surgery and Surgical Research - Peertechz Publications, 2019)
In this paper we analyze, through a mathematical model, the potential impact of HCV antiviral therapy on the liver transplantation waiting list (LTWL) in the State of Sao Paulo, Brazil. In previous papers, we projected the size of the waiting list by taking into account the incidence of new patients per year, the number of transplantations carried out in that year, and the number of patients that died in the waiting list. In the present work, we projected the LTWL size for the next 30 years and we introduced the anti-HCV treatment, which was assumed to half the incidence of patients in the LTWL and that the recovery of patients in the list would triple. The liver transplantation rate was assumed to not be affected by the anti-HCV treatment. Our mathematical model demonstrates that anti-HCV therapy would have a remarkable impact on the size of the LTWL, in the State of Sao Paulo, dropping from twenty-four thousand to approximately twelve hundred patients in the next 30 years.